Command and prohibition forms and its implication according to usuliyyun: An applied study toward fatawa of Jama'ah al-Takfir Wa al-Hijrah / Khalid Hindi K Alharbi - Khalid Hindi , K Alharbi (2016)
This thesis studies the command and prohibition forms and its implication According to usuliyyun (Scholars of the principles of jurisprudence) an applied study toward fatwa of jama’ah Al-takfir wa Al-hijra "Excommunication and Exodus” group) through an examination and analysis of the implications and phrasing mentioned in the verses of the Qur’an and hadith, related to this matter. To that purpose is utilized: a review of the books of the principles of jurisprudence, scrutiny of the views of scholars on the mentioned wordings and their implications and a discussion on them by means of stating examples from the Qur’an and Sunnah. Later, an exposé of the danger of the mix-up of these wordings and implications on the individual and society in these texts is addressed. The study aims at finding the implicit wordings in the Islamic legal text so as to exploit them in the interpretation of the wordings of the injunctive discourse, stated in the Islamic legal text. Other objectives would be to constrain farfetched understanding of the Islamic legal texts, which could lead to religious fanaticism, and prevent misinterpretation of the Shariah’s texts through undermining the legal rulings and permitting the prohibited, under the pretext that The Legislator (Allah Almighty) has not obligated averting that prohibited in His Book. The study also aims to analyse the approach of the Takfir wal-Hijra (Excommunication and Exodus) group, through the wordings and implications of the explicit injunctions and prohibitions as well as the implicit ones, as mentioned in the Islamic legal text; the purpose is to comprehend and refute scholastically, away from extremism, the confusion into which this group has fallen when releasing its fatwas. Two approaches were adopted in this study: the method of collecting the material through the library, and the process of data analysis, by which the scholastic substance is applied to the fatwas of the group of Takfir wal-Hijra (Excommunication and Exodus). The Quranic verses and ahadith on which the group relies and misinterprets are also exposed with the right interpretation, and the group’s false deductions are addressed. The study was concluded with some of the findings; they hold that the scholars of the principles of jurisprudence did not articulate the implicit wordings, indicating injunction or prohibition, by single expressions as was the case with the explicit ones; the researcher mentioned the reason. Furthermore, ignorance of the wordings and their meanings generates extremist thought or radical jurisprudence in the rulings of religion and Islamic legal texts and their objectives. The consequences lead to labeling people with transgression, innovation, and infidelity of designated individuals; all of that, on account of the misinterpretation of the wordings of injunction and prohibition and their implications in the Qur’an and Sunnah. In addition, the study concluded that the main causes of the emergence of this group and it deviant ideology are: first, the oppression and persecution faced by those who affiliated themselves to Islam; second, the ignorance of the wording and meaning of the legal Islamic text; third, the ethical chaos and divergence in the schools of thought.